1988
DOI: 10.1128/jb.170.6.2618-2624.1988
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the cell-associated region of group A streptococcal M6 protein

Abstract: DNA sequence analysis of the complete M6 protein gene revealed 19 hydrophobic amino acids at the C terminus which could act as a membrane anchor and an adjacent proline-and glycine-rich region likely to be located in the cell wall. To define this region within the cell wall and its role in attaching the molecule to the cell, we isolated the cell-associated fragment of the M protein. Assuming that the cell-associated region of the M protein would be embedded within the' wall and thus protected from trypsin dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 32 publications
6
110
0
Order By: Relevance
“…Extensive amino acid sequence similarity between FcRA76 and M proteins in their signal peptides was observed. The deduced amino acid sequence also indicated that FcRA76 contains a proline-rich region and a portion of a C-terminal membrane anchor sequence, both similar to that of M6 and M24 proteins (10). From these results, we postulated that streptococci retain a superfamily of genes that encode surface proteins with heterologous functions: a family of immunoglobulin receptors and a family of antiphagocytic M proteins.…”
mentioning
confidence: 80%
“…Extensive amino acid sequence similarity between FcRA76 and M proteins in their signal peptides was observed. The deduced amino acid sequence also indicated that FcRA76 contains a proline-rich region and a portion of a C-terminal membrane anchor sequence, both similar to that of M6 and M24 proteins (10). From these results, we postulated that streptococci retain a superfamily of genes that encode surface proteins with heterologous functions: a family of immunoglobulin receptors and a family of antiphagocytic M proteins.…”
mentioning
confidence: 80%
“…The two Fn-binding proteins of S. dysgalactiae have characteristics typical of cell-wall-associated proteins of Gram-positive cocci (Guss et al, 1990;Hollingshead et al, 1986;Pancholi and Fischetti, 1988). Sequences characteristic of signal peptides are present and both proteins have similar hydrophobic membrane spanning domains and COOH-terminal basic residues.…”
Section: Discussionmentioning
confidence: 99%
“…The upstream region is a unique sequence of approximately 50 amino acids called X,, (starting at residue 763) of which 16 amino acids are prolines. Downstream of the R, region, the proline residues are again more frequent than in the rest of the protein, which is typical for the cellwall-spanning domain (W,) of cell-surface proteins in Grampositive cocci (Pancholi and Fischetti, 1988).…”
Section: Nucleotide Sequences Of Fnba and Fnbb And The Deduced Amino mentioning
confidence: 99%
“…This position precludes selection for variant antigens by antibody surveillance. Furthermore, these authors (44) suggest that the structure of this region is important in stabilizing the M protein molecule in the cell wall. Thus, mutations in this region would probably be selected against.…”
Section: Discussionmentioning
confidence: 99%
“…Protease protection studies with the M6 molecule showed this region to be embedded in the cell wall (44). This position precludes selection for variant antigens by antibody surveillance.…”
Section: Discussionmentioning
confidence: 99%